Pengaruh Leverage dan Likuiditas terhadap Nilai Perusahaan dengan Pemoderasi Umur Perusahaan - Rina Nopianti; Mochamad Fahru Komarudin; Leni Triana (Politeknik Ganesha Medan, 2023)
This study aims to explore how leverage and liquidity affect the value of companies listed on the Indonesia Stock Exchange from 2018 to 2022. Firm age is also considered a moderating variable in the analysis, using a sample of 15 companies using SPSS 23.0 for quantitative data analysis. Secondary data were used which were obtained from annual reports taken from the respective company websites and the website of the Indonesia Stock Exchange (IDX). The research population consists of banking companies listed on the IDX in the 2018-2022 period. The results of the study found that leverage has a significant negative effect on firm value, while the liquidity ratio has no significant effect. In addition, firm age was found to moderate the relationship between leverage and firm value, but not the relationship between liquidity and firm value. The analysis shows that the combined leverage ratio and liquidity account for 81.9% of the variance in firm value, with the remaining 18.1% being influenced by other variables not included in the study. It can be concluded that leverage has a significant negative effect on firm value, while liquidity has no impact on firm value. In addition, firm age can moderate the relationship between leverage and firm value, but not moderate the relationship between liquidity and firm value in companies listed on the Indonesia Stock Exchange. This study provides valuable insights, emphasizing the importance of firm age as a moderating variable in the relationship between leverage and firm value.